High-Voltage Topological Architecture-Based Energy Management Strategy of the Plug-In Hybrid Powertrain System - Ziliang Zhao; Jun Zhao; Bin Guo; Rifei Lai (Complexity)
Hybrid technology (including plug-in hybrid) integrates the advantages of traditional automobile technology and pure electric technology, which can greatly reduce fuel consumption and improve emissions. It has become one of the main technologies developed at present and in the next 15∼20 years. Energy management is the core algorithm of hybrid electric vehicle control strategy, and it is the focus of current research. However, these studies mainly focus on the high efficiency of control assembly, optimal management of power system energy, and maximum recovery of renewable energy but have not considered energy distribution management and optimization between the power battery and the low-voltage battery. Hence, based on the high-voltage topology of the plug-in hybrid system, this paper proposes the optimal energy management strategy between the power battery and the low-voltage battery under different working conditions. The charging and discharging characteristics of the power battery under different electric quantities are also combined. The experimental results show that based on the optimized energy management strategy, the pure electric driving range is increased by 6% under NEDC condition for a C-class plug-in hybrid car, and the energy-saving effect of the vehicle is further improved.